Fluid resuscitation in critically ill patients: a systematic review and network meta-analysis - Liu C; Mao Z; Hu P; Hu X; Kang H; Hu J; Yang Z; Ma P; Zhou F (Dove Medical Press, 2018)
Chao Liu,1,* Zhi Mao,1,* Pan Hu,1,* Xin Hu,1 Hongjun Kang,1 Jie Hu,1 Zhifang Yang,2 Penglin Ma,3 Feihu Zhou1,4 1Department of Critical Care Medicine, Chinese People’s Liberation Army General Hospital, Beijing, People’s Republic of China; 2Beijing Institute of Pharmacology and Toxicology, Beijing, People’s Republic of China; 3Department of Critical Care Medicine, the 309th Hospital of Chinese People’s Liberation Army, Beijing, People’s Republic of China; 4National Clinical Research Center for Kidney Diseases, Chinese People’s Liberation Army General Hospital, Beijing, People’s Republic of China *These authors contributed equally to this work Objective: The aim of this study was to compare the effectiveness of different fluids on critically ill patients who need fluid resuscitation through a systematic review and network meta-analysis (NMA). Data sources: Electronic databases were searched up to March 2018 for randomized controlled trials comparing the effectiveness of different fluids in critically ill patients. The primary outcome was mortality, and the secondary outcomes were the incident of acute kidney injury (AKI) and risk of receiving renal replacement therapy (RRT). A Bayesian NMA was conducted, and the quality of evidence contributing to each network estimate was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) Working Group criteria. Results: We deemed 49 trials eligible, including 40,910 participants. The quality of evidence was rated as moderate in most comparisons. There was no significant difference among resuscitation fluids in mortality. NMA at the 9-node level showed the most effective fluid was balanced crystalloid (BC) (80.79%, the ranking of resuscitation fluid based on cumulative probability plots and surface under the cumulative ranking curves [SUCRAs]). NMA at the 10-node level showed that the most effective fluid was Plasma-Lyte (77.52%). Results of sensitivity analyses in mortality did not reveal any significant changes in the findings for primary outcomes. High-molecular-weight hetastarch (H-HES) was associated with an increased incidence of AKI when compared with gelatin (odds ratio [OR], 0.43; 95% credibility interval [CrI], 0.19–0.94), low-molecular-weight hetastarch (L-HES; OR, 0.50; 95% CrI, 0.30–0.87), BC (OR, 0.55; 95% CrI, 0.34–0.88), and normal saline (OR, 0.56; 95% CrI, 0.34–0.93). Meanwhile, H-HES was also associated with an increased risk of receiving RRT when compared with BC (OR, 0.51; 95% CrI, 0.27–0.93) and normal saline (OR, 0.52; 95% CrI, 0.24–0.96). Conclusion: BCs, especially the Plasma-Lyte, are presumably the best choice for most critically ill patients who need fluid resuscitation. Meanwhile, the use of H-HES was associated with an increased incidence of AKI and risk of receiving RRT. Registration: PROSPERO (CRD42017072728). Keywords: fluid resuscitation, critically ill, crystalloids, colloids, systematic review, network meta-analysis